Endoscopic Diagnosis of Superficial Gastric Cancer for ESD - Oyama, Tsuneo (Springer Japan : Imprint: Springer, 2016)
This book focuses on the preoperative diagnosis of early-stage gastric cancer, presenting various cases and their diagnoses using Endoscopic Submucosal Dissection (ESD), a new technique for dissecting early-stage gastric cancer. The first chapter presents different cases with precise explanations and observations, thus providing basic knowledge of invasion depth diagnosis, diagnostic coverage, and qualitative diagnosis. The second part of this book further expands on these topics with more examples and current practices before concluding with an in-depth look at the application in difficult-to-treat cases, complete with a vast range of figures and detailed diagnoses. Edited and authored by pioneering researchers in the field, Preoperative Diagnosis of Gastric Cancer is designed as a textbook for clinicians and professionals in the fields of endoscopy and gastroenterology.